Activating and Guiding the Engagement of Seniors With Online Social Networking: Experimental Findings From the AGES 2.0 Project. (January 2018) - Morton, Thomas A.; Wilson, Neil; Haslam, Catherine; Birney, Megan; Kingston, Rosemary; McCloskey, Lauren-Grace
Objective: Guided by theoretical and empirical work attesting to the health benefits of social connections, we tested whether Internet connectivity, and training in its use for social purposes, can support the well-being of older adults receiving care.Method: Participants ( N = 76) were randomly assigned to receive 3 months training versus care-as-usual. Cognitive and mental health were assessed before and after the intervention.Results: Results show significant cognitive improvements across time in the training, but not control, group. This effect was mediated through a combination of increased social activity, improved self-competence, and maintained personal identity strength. Indirect effects on mental health outcomes via these processes were also observed.Discussion: These findings suggest that Internet access and training can support the self and social connectedness of vulnerable older adults and contribute positively to well-being.